A Slow Outward Current Activated by FMRFamide in Heart Interneurons of the Medicinal Leech - Nadim, Farzan (J Neurosci, 1997)
The endogenous neuropeptide FMRFamide (Phe-Met-Arg-Phe-NH(2)) can accelerate the oscillation of reciprocally inhibitory pairs of interneurons that pace heartbeat in the medicinal leech. A model based on all available biophysical data of a two-cell heart interneuron oscillator provides a theoretical basis for understanding this modulation. Previously observed modulation of K(+) currents by FMRFamide cannot account for this acceleratory effect in the model. This observation prompted the present reexamination of K(+) currents in heart interneurons. We devised better methods for separation of the various components of K(+) current and more accurately measured their activation and deactivation kinetics. Moreover, we demonstrated that FMRFamide activates a previously undetected K(+) current (I(KF)), which has very slow activation and deactivation kinetics. Addition of physiologically measured amounts ofI(KF) to the model two-cell oscillator can account for the acceleratory effect of FMRFamide.